1982
DOI: 10.1128/jb.151.2.989-995.1982
|View full text |Cite
|
Sign up to set email alerts
|

Uptake hydrogenase activity and ATP formation in Rhizobium leguminosarum bacteroids

Abstract: The role of uptake hydrogenase was studied in Rhizobium leguminosarum bacteroids from the nodules of Pisum sativum L. cv. Homesteader. Uptake hydrogenase activity, measured by the 3H2 uptake method, was dependent on C( consumption and was similar to H2 uptake measured by gas chromatography. z Km for 02 of 0.0007 atm (0.0709 kPa) and a Km for H2 of 0.0074 atm (0.7498, kPa) were determined. H2 increased the rate of endogenous respiration by isolates with uptake hydrogenase (Hup+) but had no effect on an isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Hydrogen enhances respiration in R. japonicum bacteroids [62]. In bacteroids of Hup + R. leguminosarum strains [63] and in bacteroids of R. japonicum [64], hydrogen increased the level of oxygen, optimal for acetylene reduction. These authors conclude that a major function of hydrogen oxidation is to provide respiratory protection of the nitrogenase proteins against oxygen.…”
Section: Physiology Of Hydrogen Uptakementioning
confidence: 98%
“…Hydrogen enhances respiration in R. japonicum bacteroids [62]. In bacteroids of Hup + R. leguminosarum strains [63] and in bacteroids of R. japonicum [64], hydrogen increased the level of oxygen, optimal for acetylene reduction. These authors conclude that a major function of hydrogen oxidation is to provide respiratory protection of the nitrogenase proteins against oxygen.…”
Section: Physiology Of Hydrogen Uptakementioning
confidence: 98%
“…Hup determinants of these strains may, therefore, differ significantly from the "R. japonicum-type" hup sequences found in the other Hup ÷ strains of R. leguminosarum. These two strains, as well as 128C13, which hybridized only weakly to the hupspecific probes, have all been shown to couple H 2 oxidation to ATP formation in bacteroid preparations [5]. The only coupled strain tested which showed strong hybridization was 175R1.…”
Section: Comparison Of the Hup Regions Of R Leguminosarum Strainsmentioning
confidence: 95%
“…Only a few strains of R. leguminosarum appear to be Hup+, and in these there is insufficient activity to recycle all the H 2 produced during N 2 fixation [3,4]. A physiological characterization of a numer of Hup + strains of R. leguminosarum indicated that Hup activity varied among strains and that H 2 oxidation was strongly coupled to ATP formation in only a few strains [5].…”
Section: Introductionmentioning
confidence: 99%
“…Weber, USDA, Beltsville, MD, U.S.A. Strain 6-8 was one of several Hup -mutants isolated after ethyl methane sulfonate (EMS) mutagenesis of 3Ilb 110 using a procedure similar to that described by Maier [6] for the isolation of Rhizobium japonicum mutants unable to grow chemolithotrophically on H 2. This strain did not show any hydrogenase activity when tested using the tritium uptake assay [7,8] and H 2 uptake when monitored by gas chromatography [7].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 97%
“…H 2 uptake was monitored using the tritium 0378-1097/83/0000-0000/$03.,00 © 1983 Federation of European Microbiological Societies uptake assay as described previously [7,8], and also by monitoring H 2 consumption using gas chz,~matography (Varian Aerograph model 920, equipped with a thermal conductivity detector and molecular sieve column (0.5 nm)) with N 2 as the carrier gas.…”
Section: H 2 Uptake Assaymentioning
confidence: 99%